The Symbolical Interaction of Inter Dance Performers in Hak-Hakan performance in The Ritual Ceremony in Kaliyoso, Tegalombo, Kalikajar, Wonosobo - Handayani, Setyati Dyah; Jazuli, Muhammad; Utomo, Udi (Catharsis, 2018)
Hak-hakan is a traditional art included as the part of Hak-Hakan ritual in Kaliyoso Village, Tegalombo, Kalikajar, Wonosobo. Hak-hakan reflects the history of the establishment of Kaliyoso Village from the opening of the area, creating water channel (wangan), until the creation of Kaliyoso Village. This research aimes to describe Hak-hakan as the interaction media between societies as well as the meaning of Hak-Hakan in ritual ceremony. This research was a qualitative research. The technique of collecting data was using observation, interview, and document. The techniques of analyzing data were data reduction, data presentation, and conclusion. The result of the research showed that Hak-hakan became the media of interaction in the rituals through; First, the interaction of the society to their ancestors from the offerings during the preparation and the execution of the performance; and Second, is the interaction between art performers which happens between leaders and dancers and between dancers through symbols of Hak-hakan, including movement, male dancers, and dialogue. The movements of this art are nglamak tumeka pelusan, mangkat babat babat, ngratakke lamak, pasang gebal, tayuban. Dialogue is executed in the form of talks to each other initiated by the shout of the leader (pelandang) then continued with questions and answer and invitation through discussion for working together to open the area. The meaning of Hak-hakan is contained in the symbol of the offerings, movements, male dancers, and dictions.